Equitable redistribution without taxation: A lesson from East Asian miracle countries - Md. Arifur Rahman (Luxembourg Income Study (LIS), 2018)
Does uncertainty of labor earning over the life-time increase income inequality? - This paper finds that there is a direct positive relationship between life-time uncertainty and income inequality. Earlier studies single out the effect of uncertainty to pin point the effects of predictable factors (i.e. education, family background, etc.), whereas the uncertainty is treated as uncontrollable factor. This paper finds that, the degree of earning uncertainty is predictable to a large extent, which is one of the corner-stones of life cycle models with stochastic earnings. Therefore, the uncontrollable uncertainty can be influenced by policy decisions. The EAM countries have set examples of such policies and have shown that despite their rapid economic growth, inequality has been decreased in those countries. The degree of earning uncertainty can be reduced by creating more jobs in less volatile Dependent Employment. In other words, by giving a worker higher opportunity to find a less volatile job, earning uncertainty can be reduced. And reduced earning uncertainty eventually results in reduced income inequality.
Keywords: D15; D33; E24; 330; Inequality; Redistribution